Upaya Guru Pendidikan Agama Islam dalam Mengatasi Kesulitan Membaca Al-Qur’an pada Peserta Didik - Fatwah Nur Azizah; Nofitayanti; Hamzah Irfanda; Aulia Fitri (Laskar Karya, 2026)
This study aims to analyze the difficulties in reading the Qur’an among eleventh-grade students at SMAN 5 Kota Pariaman, identify the internal and external factors influencing these difficulties, and evaluate the impact of the tadarus program and teachers’ efforts in addressing them. The research employed a descriptive qualitative approach using field research. Data were collected through participatory observation, semi-structured interviews with students and teachers, and documentation. Data validity was ensured through source and method triangulation, while data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the main difficulties experienced by students include incorrect pronunciation of hijaiyah letters (makhraj), improper application of tajwid rules—particularly the rules of mad—and inaccuracies in determining waqaf. Dominant internal factors include low motivation and interest, feelings of embarrassment, lack of self-confidence, and limited practice. External factors involve inconsistent teacher guidance, a less conducive classroom environment, limited time allocation for tadarus, and insufficient parental support. Nevertheless, the tadarus activity has shown positive impacts, including gradual improvement in reading accuracy and increased self-confidence among students. The study concludes that difficulties in reading the Qur’an are multidimensional; therefore, an integrated approach involving strengthened tajwid instruction, personalized mentoring, and collaboration between school and family is necessary.